FACTORS INFLUENCING POST-CIRCUMCISION WOUND HEALING - Daryanto, Besut; Satyagraha, Paksi; Kustono, Andri; Dhani, Fauzan Kurniawan; Negara, Edvin Prawira; Purnomo, Athaya Febriantyo; Sholihah, Nikmatus; Hanggara, Dian Sukma (Indonesian Urological Association, 2024)
Objective: This study aims to determine the effect of the penile gland and smegma smear, the expression of collagen and fibroblasts in the preputium, on post-circumcision wound healing. Material & Methods: A cross-sectional study conducted in Malang with samples obtained by purposive sampling on September 17, 2022. Inclusive criteria were uncircumcised males who agreed to be circumcised and had no contraindications to the procedure. Furthermore, the preputium obtained from the circumcision procedure was stained with Hematoxylin-Eosin (HE) and counted under an optical microscope. Post-circumcision evaluation was carried out seven days after the procedure. The data were analyzed using the regression method; p denotes the probability value or significance level, while the b score denotes the degree of influence. Results: There were total of 31 research samples that had a significant difference in the average age between the samples with post-circumcision complaints (11.25 ± 2.75) and those without complaints (8.5 ± 2.73) (p=0.05). The regression test found that bacterial culture, fibroblasts, and collagen had significant effects of 24%, 25%, and 24%, respectively. Conclusions: Skin elasticity decreases with age, as marked by increased fibroblasts and decreased collagen density. Fibroblast factors, collagen, and bacterial culture are significant in wound healing. Keywords: Circumcision, collagen, fibroblast, wound healing.